Abnormal PdII-Catalyzed Cyclization of 1-Methyl-1-(2-trimethylsilylethynyl)-2-propenyl Acetate - Valentin Rautenstrauch; Ulrich Burger; Philippe Wirthner (CHIMIA)
PdCl2(MeCN)2-catalyzed cyclization of 1-methyl-1-(2-trimethylsilylethynyl)-2-propenyl acetate (4) afforded 5-methyl-2-trimethylsilyl-1,4-cyclopentadienyl acetate (5) and 3-methyl-2-trimethylsilyl-1,3-cyclopentadienyl acetate (6) in a 1.2:1 ratio and ≥80% combined yield. The formation of 5 was anticipated by analogy with previous work but that of 6 is unprecedented. Compounds 5 and 6 were trapped with N-phenylmaleimide and their fate in the absence of the trapping agent elucidated.